Viabilidad de la construcción de vivienda nueva en Colombia bajo el sistema de impresión 3D (2023)
This work explores and evaluates 3D printing technology as a new construction alternative, offering an overview of its benefits and challenges in different aspects. The main objective is to develop a feasibility study on housing construction in Colombia under this system. The work is based on the review of literature related to its application in construction, in addition to a detailed analysis of housing projects that have implemented this system.